The Analysis Text Book Padha Bisa Basa Jawa Curriculum 2013 8th Grade Junior High school Yudhistira's Publisher - ambarwati, neli eki (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2018)
The purpose of the research was to describe the content feasibility, presentetion feasibility, and language feasibility on the Javanese text book Padha Bisa Basa Jawa curriculum 2013 class VIII SMP/MTs publish by Yudhistira. This study uses a qualitative descriptive approach that is evaluative. Technique of collecting data in this research by using method of refer, sort, and record. The results of this study indicate the textbook Padha Bisa Basa Jawa curriculum 2013 class VIII SMP/MTs publish by Yudhistira of the content feasibility obtained score 85,4%, the aspect of presentation feasibility obtained 82,8% score, and aspects of the language feasibility obtained score 75%. Textbook Padha Bisa Basa Jawa curriculum 2013 class VIII SMP/MTs publish by Yudhistira fall into the category worthy. Keywords: textbook, feasibility of conten, feasibility of presentation, and feasibility of language.